The relationship of Filipino stepfathers with their stepchildren - Queja, Mitzi Ann Faye N.; Santos, Mary Joshua C. (College of Home Economics, University of the Philippines Diliman, 2023)
Because of the crucial role of stepfathers in the lives of their stepchildren, this study aimed to gain an understanding of the stepfathers’ relationship with their stepchildren. Data were collected through interviews with ten Filipino cisgender stepfathers aged at least 21, who were residing with school-aged stepchildren living in the National Capital Region (NCR). Through a thematic analysis, the stepfather-stepchild relationship quality, stepfather involvement, stepfather authority, and stepfather-stepchild conflict, as well as the factors affecting the relationship were discussed. It was revealed that stepfathers act like a parent and a father towards their stepchildren based on the meanings that they created for their role. Stepfathers also willingly engage in different activities and responsibilities related to their stepchildren including providing, caregiving, bonding, disciplining, and supporting in academics. Among the factors that influence the stepfather-stepchild relationship, the encouragement of the mother and the arrival of a younger joint child affirmed the father role of the stepfather. Overall, the relationship of stepfathers with their stepchildren is just like the relationship of other types of fathers with their children and stepfathers take an active role in developing their relationship. The findings of this study will add to the discourse in clarifying the roles of stepfathers and understanding their crucial role and contribution to the lives of their stepchildren.